2021
DOI: 10.1016/j.eclinm.2021.100987
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of adults who received liver transplant as young children

Abstract: Background: Patient and graft survival 20-years after pediatric liver transplantation (pLT) are excellent. In children, attainment of normal growth, education and social adaptation to be an independent adult are equally important. This is particularly relevant for children who receive liver transplant at a young age, where infantile-onset liver disease, surgery and immunosuppression can adversely affect growth and neurodevelopment. The aim of this study was to evaluate the long-term physical and psychosocial o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 29 publications
(40 reference statements)
2
25
0
1
Order By: Relevance
“…In addition, a reporting bias may be present resulting in only the selection of available results for analysis. Finally, we note that graft and patient survival are not comprehensive measures, and registry studies have historically not included patient‐reported outcomes that define a more “meaningful survival.” [ 20 ] However, we also note that our report highlights opportunities for future efforts that could better inform the community and further improve long‐term outcomes. For one, it is notable that the percentage of living donor LTs (LDLTs) did not increase between eras.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, a reporting bias may be present resulting in only the selection of available results for analysis. Finally, we note that graft and patient survival are not comprehensive measures, and registry studies have historically not included patient‐reported outcomes that define a more “meaningful survival.” [ 20 ] However, we also note that our report highlights opportunities for future efforts that could better inform the community and further improve long‐term outcomes. For one, it is notable that the percentage of living donor LTs (LDLTs) did not increase between eras.…”
Section: Discussionmentioning
confidence: 87%
“…We agree that it is an alternative, but do not agree that it is either entirely safe or definitive. We have thus argued in our response that LT is not as safe as medical therapy and comes with its own set of problems in the long term [3,4]. We also need to remember that the reported experience is from a single center and only of 9 patients, thereby limiting its generalizability across the country [5].…”
Section: Declarationsmentioning
confidence: 94%
“…The ability to return to a near normal life is an important gauge for the success of a medical intervention. We recently showed that only a quarter of our adolescent and young adult cohort (26%) achieved a composite outcome of ‘meaningful survival’ 20 years after liver transplantation52 (table 2).…”
Section: Adolescents As Childhood Recipients Of Liver Transplantationmentioning
confidence: 96%